Estudio de la arquitectura y funcionalidad de la Huaca Sacachique, en el distrito de Laredo - Valverde Segura, Yajaira Jackelin (2023)
This work has focused on the analysis of the architectural structure in the Huaca Sacachique, in the Moche valley. Archaeological prospecting work has allowed us to identify that this huaca has a huge architectural structure, it was built by the Cupisnique social group using conical adobes and stones during the Middle Formative Period. Apparently, Huaca Sacachique presented a plan in the shape of a "U" according to the architectural pattern that was developed in the formative. This period allowed large adobe structures to be built in the Moche valley, new irrigation systems were built due to the increase in population due to the migration of coastal social groups that settled in the surroundings of Sacachique and the Caballo Muerto complex. The functionality of the huaca was related to these phenomena that occurred in the Formative period.